2016
DOI: 10.1097/mnh.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis

Abstract: Purpose Atherosclerotic renovascular disease remains highly prevalent and presents an array of clinical syndromes. Recent prospective trials have dampened enthusiasm for revascularization generally, but clinicians recognize the need to identify patients likely to benefit from vascular intervention. Recent findings highlight the inflammatory nature of vascular occlusive disease and the limits of the kidney to adapt to reduced blood flow. Although moderate reductions can be tolerated, severe impairment of rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…11 Importantly, patients with atherosclerotic renal artery stenosis presenting with rapidly declining kidney function with bilateral atherosclerotic renal artery stenosis or stenosis to a solitary functioning kidney should be considered for revascularization to preserve kidney function. 12 …”
Section: What Should Clinicians and Researchers Do?mentioning
confidence: 99%
“…11 Importantly, patients with atherosclerotic renal artery stenosis presenting with rapidly declining kidney function with bilateral atherosclerotic renal artery stenosis or stenosis to a solitary functioning kidney should be considered for revascularization to preserve kidney function. 12 …”
Section: What Should Clinicians and Researchers Do?mentioning
confidence: 99%
“…As with all forms of hypertension, the overall goal of managing RVH is to reduce the morbidity and mortality associated with elevated BP [ 20 ]. In patients with ARAS, invariably associated with systemic atherosclerosis, atherosclerotic risk factor must be controlled, and lifestyle modification must be implemented, including smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the modulation of the renin–angiotensin system in patients with RAS secondary to solitary functioning kidney or severe bilateral stenoses has the potential to dramatically decrease GFR and induce AKI and to reduce perfusion pressure so low as to induce ischemic nephropathy in pressure-dependent kidneys. Therefore, ACE inhibitors and sartans are contraindicated in those patients [ 20 ]. Some drawbacks of pharmacotherapy and the presence of patients with severe RAS refractory to the abovementioned hypotensive drugs were the impetus for the development of more permanent and decisive solutions such as surgical and percutaneous revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hypoxia is characterized by microvascular rarefaction leading to irreversible damage to the renal parenchyma. In fact, clinical studies have reported that even after resolution of stenosis through angioplasty, the recovery of renal function is limited, and patients often progress to end-stage chronic renal disease [ 5 8 ]. In addition, during unilateral renal stenosis, the contralateral kidney is constantly exposed to high blood pressure and exhibits structural and functional features of a hypertensive kidney.…”
Section: Introductionmentioning
confidence: 99%